Assessment of insomnia and sleep quality among patients with Type 2 diabetes - Srjana Karumanchi; Venkata Rambabu Mallela; Krishna Chaitanya Alam; Amith Kumar Pendurthi; B S. V. Manjula; Ananya Pakalapati (Wolters Kluwer Medknow Publications, 2023)
Background: Type 2 diabetes and insomnia are common health issues which have a detrimental relationship with each other. Clinical management of diabetes in patients with poor sleep quality is a challenge. Therefore, understanding the correlation between the diabetic status, the presence of diabetes-related complications, and poor sleep quality among diabetic patients can help physicians in the better management of such cases. Objective: The objective of this study was to study the sleep quality among patients with type 2 diabetes. Materials and Methods: A cross-sectional study was carried out among 200 patients with type 2 diabetes. "The Pittsburgh Sleep Quality Index (PSQI)" questionnaire was used to document the quality of sleep. HbA1c and fasting blood sugar were estimated. Complications of diabetes were assessed using investigations such as electrocardiography, urine albumin, and other relevant investigations as and when indicated. Type of treatment was recorded from the preexisting prescription. Binary logistic regression analysis was used to calculate the adjusted odds ratio. Results: The mean age was 55.08 ± 13.02 years. Forty-five percent reported fairly good subjective sleep quality. 26.5% had 31-60 min sleep latency. Fifty-one percent had sleep duration of more than 7 h. Habitual sleep efficiency was >85% in 82.5% of study participants. 58.5% had sleep disturbances for less than a week. Ninety-five percent did not use any sleep medication and 62% had no daytime dysfunction during the past month. The prevalence of poor sleep quality was 52%. Among all the factors studied for association with poor sleep quality, only the presence of complications of diabetes were found to be significantly associated with poor sleep quality after adjusting for other factors (adjusted odds ratio = 4.33; 95% confidence interval = 2.13-8.78; P = 0.000). Conclusion: The prevalence of poor sleep quality among diabetics in the present study was high. This association was noted only with the presence of complications of diabetes. Hence, efforts to prevent complications of diabetes by regular follow-up and appropriate treatment along with regular screening for complications can prevent complications associated with diabetes and hence prevent poor sleep quality.